Efficacy and toxicity of neoadjuvant radiotherapy with concomitant dose escalation for rectal cancer - Wang, Peng; Liu, Kai; Liu, Xiaoliang; Wang, Weiping; Liu, Dingchao; Wang, Yidi; Sun, Shuai; Hu, Ke (Frontiers in Oncology, 2025)
ObjectiveThis study aimed to evaluate the efficacy of a neoadjuvant radiotherapy regimen featuring a concomitant dose escalation regimen, followed by surgery, in patients with rectal cancer.MethodsWe reviewed the clinical records of rectal cancer patients who received neoadjuvant chemoradiotherapy or radiotherapy alone with a concomitant dose escalation regimen (55–56 Gy) between October 2012 and January 2019. Chemotherapy regimens included capecitabine monotherapy or capecitabine combined with oxaliplatin. Surgery was performed 8–10 weeks after radiotherapy. Primary endpoints included the pathological complete response (pCR) rate and sphincter preservation rate. We also analyzed the impact of radiotherapy-to-surgery interval on pCR rates. Disease-free survival (DFS) was compared between pCR and non-pCR patients.ResultsA total of 415 patients were included, with 14 patients received radiotherapy alone. Following neoadjuvant therapy with concomitant dose escalation and subsequent surgery, 99 patients achieved pCR, yielding a pCR rate of 23.9%. A complete primary tumor response (ypT0) was observed in 105 patients (a TpCR rate of 25.3%), while a nodal complete response (ypN0) was achieved in 335 patients (an NpCR rate of 80.2%). Among the 369 patients who underwent lymph node dissection, 295 achieved NpCR. Sphincter preservation was achieved in 359 (86.5%) patients The incidence of grade 3 or higher acute hematologic, gastrointestinal, and genitourinary toxicities was 9.7%, 4.2%, and 1.5%, respectively. With a median follow-up of 5.06 years, an interval between radiotherapy and surgery > 10 weeks was associated with a higher pCR rate (p=0.037) after adjusting for age and sex. Patients achieving pCR demonstrated significantly better DFS compared to non-pCR patients (83.33% vs. 62.55%, p=0.0224), and this difference remained significant in stage III patients (79.15% vs. 58.35%, p=0.0308).ConclusionNeoadjuvant chemoradiotherapy with concomitant dose escalation yields high pCR rates for both primary tumor and nodal disease, with acceptable toxicity, in a significant number of patients with rectal cancer. Presence of pCR is associated with markedly improved DFS. Moreover, prolonged interval between neoadjuvant radiotherapy and surgery correlates with elevated pCR rates.